Changes in the effects of monetary policy on disaggregate price dynamics - Christiane Baumeister; Philip Liu; Haroon Mumtaz (Bank of Canada, 2012)
We examine the evolution of the effects of monetary policy shocks on the distribution of disaggregate prices and quantities of personal consumption expenditures to assess the contribution of monetary policy to changes in U.S. inflation dynamics. Given that the transmission of monetary policy to aggregate inflation is determined by the responses of its underlying components, the degree of monetary non-neutrality is ultimately the result of relative price effects at the sectoral level. We provide evidence of considerable heterogeneity in sectoral price responses by introducing time variation in a factoraugmented vector autoregression model. Over time the majority of individual prices respond negatively after a contractionary monetary policy shock and the price dispersion diminishes. We link these empirical findings to a multi-sector DSGE model and show that they are consistent with firms' heterogeneous pricing decisions and changes in the importance of the cost channel of monetary policy and the degree of wage flexibility.
Keywords: E30; E32; 330; Transmission of monetary policy; Econometric and statistical methods